The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.2147/opth.s32274
|View full text |Cite
|
Sign up to set email alerts
|

Profile of ocriplasmin and its potential in the treatment of vitreomacular adhesion

Abstract: The recent approval by the US Food and Drug Administration of ocriplasmin for the treatment of symptomatic vitreomacular adhesion (VMA), often associated with vitreomacular traction (VMT) and macular hole (MH), has brought new attention to the field of pharmacologic vitreolysis. The need for an enzyme to split the vitreomacular interface, which is formed by a strong adhesive interaction between the posterior vitreous cortex and the internal limiting membrane, historically stems from pediatric eye surgery. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 87 publications
0
8
0
Order By: Relevance
“… 21 , 24 In this series, all eyes with successful MH closure had a baseline MH diameter of within 250 μ m. Three of the 5 Stage 2 MH that failed to close had a baseline diameter of >250 μ m. The successful closure of small MH with PVL is consistent with previous reports. 21 , 24 , 25 Previous published studies on ocriplasmin 14 , 15 , 36 also showed an increased success rate for resolving MH of <200 μ m in diameter.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“… 21 , 24 In this series, all eyes with successful MH closure had a baseline MH diameter of within 250 μ m. Three of the 5 Stage 2 MH that failed to close had a baseline diameter of >250 μ m. The successful closure of small MH with PVL is consistent with previous reports. 21 , 24 , 25 Previous published studies on ocriplasmin 14 , 15 , 36 also showed an increased success rate for resolving MH of <200 μ m in diameter.…”
Section: Discussionmentioning
confidence: 88%
“…Ocriplasmin (Jetrea; ThromboGenics NV, Leuven, Belgium) seemed to fulfill such a niche when pilot studies and the Trial of Microplasmin Intravitreal Injection for Non-surgical Treatment of Focal Vitreomacular Adhesion (MiVI-TRUST) Trials (TG-MV-006 and TG-MV-007) showed its promotion of a posterior vitreous detachment (PVD). 14 , 15 Ocriplasmin was approved by the Food and Drug Administration for treatment of symptomatic VMT in 2012. The intravitreal administration of this recombinant protein composed of the catalytic domain of human plasmin provides a potential advantage over a vitrectomy for treating VMT because its injection is performed in the office setting.…”
mentioning
confidence: 99%
“…Considering its ability to induce PVD, other ophthalmic conditions and pathologies related to VMA might benefit from ocriplasmin intravitreal injection, i.e. DME, ARMD, vitreoretinal surgery, uveitic macular edema, pediatric eyes before vitrectomy; nevertheless, first results were not as satisfying as the ones achieved in the treatment of VMA [ 14 , 15 ]. Further research is needed to better understand the clinical indications, visual improvement and, most of all, potential interactions with other medications.…”
Section: Discussionmentioning
confidence: 99%
“…It is a stable, truncated form of plasmin and has several advantages over plasmin including its stability and smaller size, hence increased ability to penetrate tissues. [18] Its use as an intravitreous injection (125 μg) has been studied in two phase III randomized controlled trials for symptomatic vitreomacular adhesion (VMA) and vitreomacular traction (VMT)[19] and approved for use in more than 50 countries. The MIVI-TRUST study reported VMT release in 26.5% and closure of small full-thickness macular holes in 40.6%.…”
Section: Surgical Techniquesmentioning
confidence: 99%